A Novel Fast-EIS Measuring Method And Implementation for Lithium-ion Batteries - Lu, Pengfei; Li, Ming; Zhang, Liqiang; Zhou, Liqin (2019 Prognostics and System Health Management Conference (PHM-Qingdao), 2019)
Energy store batteries play very important roles in the marine energy power station. Monitoring batteries' state for PHM study is necessary. Electrochemical Impedance Spectroscopy (EIS) is commonly used in battery state monitor. It can acquire detailed health features of batteries. This paper purposes a Fast-EIS measuring method, including the hardware design and frequency-mixing measuring algorithm based on the Fast Fourier Transformation (FFT). It can measure the EIS with a frequency range from 0.01Hz to 10kHz, and reduce 2/3 of the measuring time compared to the commercial electrochemical workstation, with enough accuracy. This method is suitable for implementation and engineering applications.